ALADPA : Snake in the Heart - Madhavan, Suresh; Sathish, Gargi; Jayaprasad, N (Nepalese Heart Journal, 2015)
Anomalous origin of left coronary artery from pulmonary artery may or may not be associated with structural heart disease. Most of the patients with such coronary anomaly will succumb unless diagnosed and treated early. We are reporting a patient with this anomaly in seventh decade which is extremely rare. DOI: http://dx.doi.org/10.3126/njh.v12i1.12341 Nepalese Heart Journal Vol.12(1) 2015: 27-30